Pentingnya Pembelajaran Bahasa Indonesia di Perguruan Tinggi - Khoiriyah Sari; Gilang Hizbullah; Edi Syaputra (Universitas Dehasen Bengkulu, 2022)
This paper aims to motivate academics about the importance of learning and understanding Indonesian properly. It is suspected that many students and the Indonesian people are used to speaking the language without following the correct language rules. The correct language is a language that ideally obeys the rules completely. The accuracy of the rules of grammar, intonation, and expression is an absolute component that must be met by the speaker. This correct language is used in formal situations which tend to be rigid and one-way in spoken situations. For example, giving a speech that truly adheres to the principles of the rules. Meanwhile, a good language is a language that fits the situation and conditions of the conversation. It is a shared responsibility regarding the existence of the Indonesian language in this beloved country, especially academics and education practitioners.